The PaaX Repressor, a Link between Penicillin G Acylase and the Phenylacetyl-Coenzyme A Catabolon of Escherichia coli W - Galán, Beatriz (American Society for Microbiology, 2004)
The pac gene, encoding the penicillin G acylase from Escherichia coli W, is regulated by the PaaX repressor of the phenylacetate catabolic pathway. pac expression depends on the synthesis of phenylacetyl-coenzyme A. PaaX and the cyclic AMP receptor protein (CRP) bind in vitro to the Ppac promoter region. A palindromic sequence proposed as the PaaX operator is located upstream of the −35 box overlapping a CRP binding site, an unusual position that suggests a novel regulatory mechanism.